Comparison on diagnostic results of clinical, radiological and computed tomography of stifle joint in dogs - Nil Aracı; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
Aim: It is aimed to compare clinical, radiological and computed tomography findings of knee joint lesions in terms of diagnosis. In addition, early diagnosis of cranial cruciate ligament defects were assessed for effectiveness of computed tomography. Materials and Methods: 12 medium / large dogs with different breed, sex, age and breed were used as study materials. After the clinical examinations, Hudson Visual Analogue Scale and Canine Brief Pain Inventory were performed. In dogs, a force platform was used to measure unequal weight distribution in the extremities. Three positions of radiographic examination (standing cranio-caudal (CrCa), medio-lateral (ML), tibial compression mediolateral (ML)) was performed. For this purpose, mobile x-ray machine and fixed x-ray equipment were used. Computed tomography was used for tomographic examinations. Statistical analysis of the obtained data was expressed as %. Walking, pain and force platform results of arithemtic averages were used. Results: The problematic extremity was determined for according to the results of clinical examination and force platform of the cases. In some cases, pressure over the ligamentum collaterale mediale level showed that joint effusion on the extremity. Cranial displacement of tuberositas tibia was noted with the tibial compression test. Condylus medialis and lateral femoris were markedly narrowed with radiographically, art. genu of two cases were detected osteophytic production. In most of the cases, cranial rotation of the tibia was seen. Osteophyte production were identified in 1 case with computed tomographic examination. Conclusion: Especially for the identification of osteophytic production, cranial displacement of tuberosity tibia, diagnosis of patellar luxation in in Art. genu could be diagnosed by x-ray. Diagnosis of patellar luxation and cranial displacement of tibia is also observed with CT scan directly. But, CT is useful in revealed for knee joint problems. However, the taking of the sections, the modernization of the instrument should always affects the visuality.